THE ROLE OF TRAINING AND LEADERSHIP ON PERFORMANCE THROUGH COMPETENCE AT REGIONAL DRINKING WATER COMPANY IN MOJOKERTO - R.Y, Novie Noordiana; Widodo, Agus Purbo (International Conference of Business and Social Sciences, 2025)
Regional Drinking Water Company (PDAM) is a company that monopolizes the distribution of water to the community or society. Consequently it is expected to be able to supply and distribute water based on the community needs. As a result, it requires competent human resources to support the performance of PDAM. In 2017-2019 there was a decline in the performance of PDAM Maja Tirta in Mojokerto City. As a whole it was determined by three performance measurement indicators, namely services, operations and human resources (HR). In the HR department, the competency of PDAM Maja Tirta City Mojokerto employees from 2017 to 2019 experienced a downward trend. These indications indicated the needs for training programs for employees in order to improve the employee competence and performance. This study aims at examining and analyzing the effect of training and leadership through competence on the performance of PDAM Maja Tirta employees in Mojokerto City. Respondents in this study were 40 employees of PDAM Maja Tirta Mojokerto City. Data analysis used Path Analysis. The results of this study showed that training and leadership had an effect on competence in PDAM Maja Tirta Mojokerto City. The training, leadership and competence affected the employee performance. The results of the indirect influence analysis also revealed that training and leadership through competence had a significant effect on employee performance at PDAM Maja Tirta Mojokerto City